(untitled) (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2021)
This article proposes a critical examination of a large part of the available theoretical corpus referring to the Argentine composer Julián Aguirre (1868-1924). In order to confirm what is currently known about this musician, we consider the importance of revisiting texts produced in the field of music criticism, musicography and musicology, published during the 20th and 21st centuries, in order to initiate an inquiry that will put his name back on the investigative agenda. Thus, we follow the theoreticalmethodological paradigms of current musicology, to begin a road map that overcomes the fragmentary state of existing studies on the subject and the unidirectional conception that still prevails about Aguirre’s oeuvre. This research is in its preliminary stages of my doctoral studies.